Factors Associated With Paroxysmal Arrhythmias in Ambulatory ECG Monitored Patients - Dwiyanto, Yusup; Permatasari, Tria Astika Endah; Jumaiyah, Wati; Fadlilah, Siti; Sumarni, Sumarni (Scripta Medica, 2025)
Background/Aim: Arrhythmia is a heart rhythm disorder that can appear suddenly without any symptoms and has the risk of causing other diseases and even death. This study aimed to determine predicting factors for the incidence of paroxysmal arrhythmias. Methods: This retrospective observational cohort study used patients’ medical records in the Cardiovascular Outpatient Service Unit at RSUD Budhi Asih, Jakarta, Indonesia, from 2017-2021. Based on inclusion and exclusion criteria, 406 patients were analysed. The occurrence of paroxysmal arrhythmias based on the doctor’s diagnosis in medical record data was divided into paroxysmal atrial, supraventricular, ventricular and atrioventricular block (AV block) arrhythmias. Data analysis used the Chi-square test. Results: A total of 39.4 % of patients had paroxysmal atrial arrhythmias. Factors associated with the occurrence of paroxysmal atrial arrhythmias were age, gender, smoking behaviour, comorbidities and heart-pumping ability. On the other hand, body mass index, hypertension and diabetes mellitus were shown to be significantly associated with paroxysmal supraventricular arrhythmias. Gender, smoking behaviour, diabetes mellitus, coronary heart disease, thyroid disease and heart pumping ability were predicting factors for paroxysmal ventricular arrhythmias. Meanwhile, only gender and heart disease were factors associated with paroxysmal AV block arrhythmias. Conclusion: Sociodemographic and individual clinical conditions were associated with paroxysmal arrhythmias. However, these factors vary according to the outbreak of the arrhythmia.